Respuesta :

Answer:

[tex]\frac{a^3b^{-2}}{ab^{-4}} = a^{2}b^{2}[/tex]

Step-by-step explanation:

Given

[tex]\frac{a^3b^{-2}}{ab^{-4}}[/tex]

[tex]a\ne 0; b \ne 0[/tex]

Required

Evaluate

[tex]\frac{a^3b^{-2}}{ab^{-4}}[/tex]

Apply the following law of indices:

[tex]\frac{x^m}{x^n} = x^{m-n}[/tex]

So, the expression becomes:

[tex]\frac{a^3b^{-2}}{ab^{-4}} = a^{3-1}b^{-2-(-4)}[/tex]

Remove brackets

[tex]\frac{a^3b^{-2}}{ab^{-4}} = a^{3-1}b^{-2+4}[/tex]

[tex]\frac{a^3b^{-2}}{ab^{-4}} = a^{2}b^{2}[/tex]

Answer:

D. a^3 b^4 / ab^2

Step-by-step explanation:

ACCESS MORE